Localisation and colocalisation of triangulated categories at thick subcategories - Inassaridze, Hvedri; Kandelaki, Tamaz; Meyer, Ralf (MATHEMATICA SCANDINAVICA, 2012)
Given a thick subcategory of a triangulated category, we define a colocalisation and a natural long exact sequence that involves the original category and its localisation and colocalisation at the subcategory. Similarly, we construct a natural long exact sequence containing the canonical map between a homological functor and its total derived functor with respect to a thick subcategory.